Effect of Enzyme Supplementation on the Performance of Broiler Finisher Fed Microdesmis puberula Leaf Meal - Esonu, B.O.; Azubuike, J.C.; Emenalom, O.O.; Etuk, E.B.; Okoli, I.C.; Ukwu, H.; Nneji, C.S. (International Journal of Poultry Science, 2004)
A thirty-five day feeding trial was conducted to evaluate the performance of broiler finishers fed Microdesmis puberula leaf meal supplemented with `SafzymeR` (a cellulolytic enzyme). Microdesmis puberula is a choice tropical browse plant. Three broiler finisher diets were formulated to contain 0.0, 12.5% Microdesmis puberula leaf meal without enzyme. and 12.5% Microdesmis puberula leaf meal with 0.10% enzyme. One hundred and twenty (120) four-week-old Hubbard broiler chicks were divided into three groups of forty (40) birds each and randomly assigned to the three treatment diets in a completely randomized design (CRD). Data were collected on feed intake, body weight gain and feed conversion ratio. There was significant difference (p0.05) from birds on leaf meal diets without enzyme supplementation. Birds on 0.0% leaf meal diet recorded the highest daily body weight gain. Feed conversion ratios of all treatment groups were comparable. The result suggests that 0.10% of the enzyme supplementation in diets containing 12.5% Microdesmis puberula leaf meal did not improve the performance of finisher broilers.